2017
DOI: 10.2135/cropsci2016.05.0308
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Nutritional and Chemical Approach to Poa Annua Suppression in Creeping Bentgrass Greens

Abstract: Creeping bentgrass (Agrostis stolonifera L.) provides an ideal putting surface for golf courses located in temperate climates but is invaded by annual bluegrass (Poa annua L.) and silvery‐thread moss (Bryum argenteum Hedw.). There are no currently registered herbicides for annual bluegrass control in bentgrass greens. Paclobutrazol and FeSO4 will suppress one or both of these pests, but research on the effectiveness of the two together has not been reported. Our objectives were to determine the effects of repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…It was previously shown that maximum or even higher than recommended PGR rates were the most effective for annual bluegrass suppression (Woosley et al, 2003). Ervin et al (2017) tested PB rates higher than those on the label in programs to eradicate Table 4. Impact of flurprimidol (FP), paclobutrazol (PB), and trinexapac-ethyl (TE) plant growth regulators applied at various rates as standalone products or two-way (FPDTE) and/or three-way (FPDPBDTE) mixtures (as described in Table 2) on average annual bluegrass cover and average creeping bentgrass injury (10 = highest) in 2017-19 at Bel-Air Country Club, Los Angeles, CA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that maximum or even higher than recommended PGR rates were the most effective for annual bluegrass suppression (Woosley et al, 2003). Ervin et al (2017) tested PB rates higher than those on the label in programs to eradicate Table 4. Impact of flurprimidol (FP), paclobutrazol (PB), and trinexapac-ethyl (TE) plant growth regulators applied at various rates as standalone products or two-way (FPDTE) and/or three-way (FPDPBDTE) mixtures (as described in Table 2) on average annual bluegrass cover and average creeping bentgrass injury (10 = highest) in 2017-19 at Bel-Air Country Club, Los Angeles, CA.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also suggested that the main factor contributing to the observed damage was the occurrence of low temperatures, which was only a minor issue in our study. Ervin et al (2017) observed both effective control of annual bluegrass and voids in the turf canopy due to the use of an aggressive PB program. Although it was not an issue in our trial, such a risk should also be considered when using PGRs.…”
Section: Creeping Bentgrass Injurymentioning
confidence: 96%
See 1 more Smart Citation
“…However, Ervin et al (2017) reported a decrease in ABG in Virginia from iron applications when N was 3.0 lb N/1000 sq ft/yr. The decrease in ABG reported by Ervin et al (2017) may be due to the 14‐day application frequency used compared with the 28‐day interval in our study. Xu and Mancino (2001) observed in the greenhouse that high application rates of Fe were more injurious to ABG than creeping bentgrass.…”
Section: Recommendations For Annual Bluegrass Controlmentioning
confidence: 95%
“…Applications of iron sulfate or “ferrous sulfate” (FeSO 4 · 7H 2 O) fertilizer reduced populations of ABG in full sun (Bell et al, 1999; Ervin et al, 2017; Han et al, 2017) but not in shaded conditions where iron applications encouraged ABG (Stiegler et al, 2003). Further investigation comparing plant growth regulator (PGR) and herbicides with treatments of FeSO 4 will help provide insight on nutritional approaches to ABG control in addition to conventional PGR and herbicide approaches.…”
Section: Useful Conversionsmentioning
confidence: 99%